Use of seed priming to improve Cd accumulation and tolerance in Silene sendtneri, novel Cd hyper-accumulator - Karalija, Erna; Selović, Alisa; Dahija, Sabina; Demir, Arnela; Samardžić, Jelena; Vrobel, Ondřej; Ćavar Zeljković, Sanja; Parić, Adisa (Ecotoxicology and environmental safety, 2021)
Changes in the environment as a result of industrialisation and urbanisation impact negatively on plant growth and crop production. Cadmium (Cd) is one of the most dangerous metals that enters the food chain, with toxic effects on plants and human health. This study evaluated the potential of Silene sendtneri as a novel hyperaccumulator and the role of seed priming in tolerance and accumulation rate of Cd. The effect of different priming agents on germination performance, root growth, seedling development, metal uptake and accumulation, antioxidant defences including enzymatic and non-enzymatic antioxidants has been assessed. Seed priming using silicic acid, proline alone or in combination with salicylic acid- enhanced germination, seedling development, and root growth under Cd stress. The same priming treatments induced an increase of water content in shoots and roots when plants were exposed to Cd. The enzymatic antioxidant response was specific for the priming agent used. An increase in ferulic acid and rutin in shoots was related to the increase of Cd concentration in the medium. The concentration of malic and oxalic acid increased significantly in shoots of plants grown on high Cd concentrations compared to low Cd concentrations. Silene sendtneri can accumulate significant levels of Cd with enhanced accumulation rate and tolerance when seeds are primed. The best results are obtained by seed priming using 1% silicic acid, proline and salicylic acid.
Keywords: Silene; Organic acids; Proline; Oxidative stress; Soil Pollutants; látky znečišťující půdu; Bioaccumulation; kyselina salicylová; kyselina křemičitá; Antioxidant defence potential; Root growth; Cadmium; Silicic Acid; Seeds; Silene sendtneri; Germination; kořeny rostlin; bioakumulace; Salicylic Acid; Phenolics; kadmium; prolin; Plant Roots; klíčení; Cd stress; semena rostlinná